VEGF Promotes Glycolysis in Pancreatic Cancer via HIF1α Up-Regulation - Shi, S.; Xu, J.; Zhang, B.; Ji, S.; Xu, W.; Liu, J.; Jin, K.; Liang, D.; Liang, C.; Liu, L.; Liu, C.; Qin, Y.; et al. (Current Molecular Medicine, 2016)
Background: Vascular endothelial growth factor (VEGF) is highly expressed in many types of tumors, including pancreatic cancer. Tumor cellderived VEGF promotes angiogenesis and tumor progression. However, the role of VEGF in glucose metabolism remains unclear. Objective: We investigated the role and the underlying mechanism of VEGF in the glucose metabolism of pancreatic cancer cells. Method: Pancreatic cancer cells were stimulated with VEGF165 for 1 or 2 h. The oxygen consumption rates (OCR) and extracellular acidification rates (ECAR) were measured using the Seahorse XF96 Extracellular Flux Analyzer. Glycolytic enzymes were detected by quantitative real-time PCR. Neuropilin 1 (NRP1) was silenced by shRNA in order to investigate its role in VEGF-induced glycolysis. Immunohistochemistry (IHC) was performed to identify the correlation among VEGF, NRP1 and hypoxia inducible factor 1α (HIF1α) in pancreatic cancer tissues. Results: VEGF stimulation led to a metabolic transition from mitochondrial oxidative phosphorylation to glycolysis in pancreatic cancer. HIF1α and NRP1 protein levels were both increased after VEGF stimulation. The down-regulation of NRP1 reduced glycolysis in pancreatic cancer cells. NRP1 and VEGF levels both correlated with HIF1α expression in pancreatic tumor tissues. Conclusion: VEGF enhances glycolysis in pancreatic cancer via HIF1α up-regulation. NRP1 plays a key role in VEGF-induced glycolysis.
Keywords: Pancreatic cancer